2017
DOI: 10.20950/1678-2305.2017v43n1p52
|View full text |Cite
|
Sign up to set email alerts
|

Colagenase de pescada branca: extração, purificação parcial, caracterização e teste de especificidade ao colágeno para aplicação industrial

Abstract: Fish processing residues are rich sources of biomolecules with industrial potential, such as enzymes with collagenolytic properties applied in the pharmaceutical, textile and leather sectors. Here, collagenolytic serine proteases were partially purified from the waste (viscera) of smooth weakfish Cynoscion leiarchus and characterized for the purpose of obtaining a value-added product from fisheries resources. The higher activity of the enzyme (72.5 U mL -1 ) was verified in optimal temperature and pH of 55°C a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
23
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 35 publications
7
23
0
3
Order By: Relevance
“…High collagenolytic activity was reported for intestinal crude extract of smooth weakfish Cynoscion leiarchus (72.5 IU/mg) [4], and Daboor et al [17] reported the collagenolytic activity (11.63 IU/mg) using a mixture of haddock, herring, flounder and ground fish crude extracts. Souchet and Laplante [28] also detected the collagenolytic activity (13.3 IU/mg) in byproducts of snow crab Chionoecetes opilio.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…High collagenolytic activity was reported for intestinal crude extract of smooth weakfish Cynoscion leiarchus (72.5 IU/mg) [4], and Daboor et al [17] reported the collagenolytic activity (11.63 IU/mg) using a mixture of haddock, herring, flounder and ground fish crude extracts. Souchet and Laplante [28] also detected the collagenolytic activity (13.3 IU/mg) in byproducts of snow crab Chionoecetes opilio.…”
Section: Discussionmentioning
confidence: 98%
“…Samples of 300 g intestine were collected, packaged in plastic containers, kept on ice and transported to the Laboratory of Enzymology, Center of Biological Sciences, Federal University of Pernambuco, Recife, Pernambuco, Brazil. The enzymatic extraction was performed according to the method described by Oliveira et al [4]. The ratio of viscera to extraction buffer (0.05 mol/L Tris-HCl, pH 7.5, containing 5 mmol/L CaC1 2 ) was 1:5 (w/v).…”
Section: Use Of Digestive Viscera and Process Of Extractionmentioning
confidence: 99%
See 3 more Smart Citations